Problematic aspects of numerical computation of the hybrid joints - Marek Rośkowicz; Jarosław Gąsior (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2020)
This paper presents the results of numerical calculations to compare the stress fields of hybrid (mechanicaladhesive) joints. ANSYS ver.19 was used as a computing tool with its solver based on finite element method (FEA – Finite Element Analysis). Based on the results obtained, a comparative analysis of the stresses in the adhesive joints for adhesives with different Young's modulus including different mounting schemes of mechanical fasteners and pressures caused by the assembly of the mechanical fasteners was performed. For modelling purposes of hybrid joints it is assumed that calculations will be made for single-lap joints where specimens with AW 2024T3 material parameters were joined. The adhesive layer was modelled by two layers of elements, adding i.a. pressure to the adherend caused by a preliminary tension of mechanical fasteners. In order to reduce the negative peeling effect at the ends of the adhesive layer, the case of mounting mechanical fasteners closer to the joint edge was also considered – at a distance of one diameter of the fitting instead of two. It has been found that using adhesive with lower value of Young's modulus can increase the load capacity of the joints due to possibility of absorbing higher loading by the mechanical fasteners. Moving the mechanical fasteners closer to the lap edge will result in a positive reduction of stress responsible for peeling of adhesive layer, as well as the pressure caused by the assembly of the bolts.This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)